Our Surgical Strategy for Thoracic Outlet Syndrome - Yasuhiro Nakajima (Neurologico Spinale Medico Chirurgico, 2018)
Surgical treatment for thoracic outlet syndrome (TOS) is a very controversial surgery because objective diagnosis, such as image and electrophysiological examination, is very difficult. Clinical provocation tests including brachial plexus compression tests, such as Morley and Roos, and vascular compression tests, such as Wright and Eden, are not high in specificity and are likely to be positive even in healthy persons and patients with carpal tunnel syndrome. We place emphasis on the laterality of latency and amplitude in the sensory neural action potential (SNAP) of the medial antebrachial cutaneous nerve and ulnar nerve. After enough stretching exercises of scapular stabilizers and brachial plexus block, we always select surgery. In this presentation, I would like to show our diagnosis method and treatment strategy including surgery.